0.125 mm3 spatial resolution steady‐state MR angiography of the thighs with a blood pool contrast agent using the quadrature body coil only at 1.5 Tesla. Issue 4 (6th February 2014) - Boschewitz, Jack M.; Hadizadeh, Dariusch R.; Kukuk, Guido M.; Meyer, Carsten; Wilhelm, Kai; Koscielny, Arne; Verrel, Frauke; Gieseke, Jürgen; Schild, Hans H.; Willinek, Winfried A.
<x xml:space="preserve">Abstract</x> Purpose To implement and evaluate high spatial resolution three‐dimensional MR contrast‐enhanced angiography (3D‐CEMRA) of the thighs using a blood pool contrast agent (BPCA) using the quadrature body coil only in patients with peripheral arterial occlusive disease (PAOD) in cases receiver coils cannot be used at 1.5 Tesla (T). Materials and Methods Nineteen patients (mean age: 68.7 ± 11.2 years; range, 38–83 years) with known PAOD (Fontaine stages; III: 16, IV: 3) prospectively underwent 3D‐CEMRA at 1.5T with a noninterpolated voxel size of 0.49 × 0.49 × 0.48 mm3. Digital subtraction angiography (DSA) was available for comparison in all patients. Two readers independently evaluated movement artifacts, overall image quality of 3D‐CEMRA, and grade of stenosis as compared to DSA. SNR and CNR levels were quantified. Results The 3D‐CEMRA was successfully completed in all patients. Patient movement artifacts that affected stenosis grading occurred in 3/38 thighs. Overall image quality was rated excellent in 15/38, good in 12/38, and diagnostic in 8/38 thighs. Stenosis grading matched with that in DSA in 35/38 thighs. High SNR and CNR were measured in all vessels. Conclusion The 0.125 mm3 spatial resolution 3D‐CEMRA of the thighs with a BPCA is feasible using a quadrature body coil exclusively with excellent image quality despite long acquisition times. J. Magn. Reson. Imaging 2014;40:996–1001. © 2014 Wiley Periodicals, Inc.